Amplitude reduction of H-reflex during mental movement simulation in elite athletes - Oishi, K.; Kimura, M.; Yasukawa, M.; Yoneda, T.; Maeshima, T. (Behavioural Brain Research, 1994)
In order to investigate the changes of motoneuron excitability during mental simulation of a voluntary movement (motor imagery; MI), the soleus H-reflex and several activities of autonomic effectors were recorded simultaneously when MI of speed skate sprint was performed. The subjects were seven elite speed skate athletes ranging in age from 18 to 24 years old. They were all skilled in MI, and could imagine full vivid skating movement internally as if they were really exercising. The subjects were awake, relaxed and blindfolded. At first, rest (5 min), positive relaxation (4 min) and concentration periods (2.5 min) were set up. Then, after the previous announcement for the start, MI was initiated by the sound of a signal gun which was recorded by a tape recorder. MIs were continued for each subject from about 36 s to 38 s, and these imaging times were very close to the actual personal best records of each subject. The autonomic effectors re presented by skin conductance response (SCR), heart rate (HR), and respiration rate (RSR) became remarkably active during MI in all trials. SCR was increased by 51% on the average. Furthermore, HR and RSR were increased by 57% and 76% respectively, compared with those during resting period. These changes in the autonomic effectors were all significant and were those which were activated in actual movements. The amplitudes of H-reflex were almost all constant before MI initiation. However, the reduction of the H-reflex amplitude arose just after the start and lasted to the end of MI. Relative values of the depressions were from 16% to 54% compared with those in rest period, and these depressions were significant statistically (P < 0.01) in all subjects and all trials. These results are discussed from the point of view of motor program. It is suggested that some descending neural mechanism which reduces the motoneuron excitability may be activated.